Desnutrición crónica y su influencia en la carcinogénesis: Un análisis exhaustivo - Mina Ortiz, Jhon Bryan; Sampedro Giler, Jeniffer Susana; Veliz Vargas , Luissana Liceth (Arandu UTIC, 2024)
Derived from the project “Educational training for nutritional malnutrition and hematological conditions in rural and urban populations in the southern zone of Manabí 2024” in the southern zone of Manabí. Malnutrition is a prevalent complication that can significantly increase morbidity and mortality in individuals of all ages, with a particularly severe impact on pediatric patients due to the specific characteristics of their development. Cancer is a global public health problem, especially in impoverished countries, every year more than 18 million people are diagnosed with cancer, and this figure is expected to rise to 29.5 million in 2040, which is why it is necessary to approach this study with the aim of investigating chronic malnutrition and its influence on carcinogenesis, whose methodology was of documentary design, The results show that severe malnutrition is frequent among cancer patients in several countries, especially among those suffering from gastroenteric and respiratory tract cancers, on the other hand, malnutrition, in its various forms, has complex biological effects on patients in different countries and the risk factors vary from country to country. It was concluded that malnutrition is closely related to a high prevalence of gastrointestinal and respiratory cancers, chronic malnutrition affects several biological mechanisms that may influence carcinogenesis, it is related to histone modifications and DNA damage, quality of life significantly influences nutrition and overall health, with recognized global impacts in different countries.